In the Crossfire of History : Women's War Resistance Discourse in the Global South - Hasanat, Fayeza S.; Asaad, Lava (Book collections on Project MUSE., 2022)
"In the global south, women have and continue to resist multiple forms of structural violence. The atrocities committed against Yazidi women by ISIS have been recognized internationally, and the Nobel Peace Prize awarded to Nadia Murad in 2018 was a tribute to honor women whose bodies have been battered in the name of race, nationality, war, and religion. In the Crossfire of History:Women's War Resistance Discourse in the Global South is an edited collection that incorporates literary works, testimonies, autobiographies, women's resistance movements, and films that add to the conversation on the resilience of women in the global south. The collection focuses on Palestine, Kashmir, Syria, Kurdistan, Congo, Argentina, Central America, Sri Lanka, and Bangladesh. The essays question historical accuracy and politics of representation that usually undermine women's role during conflict, and they reevaluate how women participated, challenged, sacrificed, and vehemently opposed war discourses that erase women's role in shaping resistance movements. The transformative mode of these examples expands the definition of heroism and defiance. To prevent these types of heroism from slipping into the abyss of history, this collection brings forth and celebrates women's fortitude in conflict zones. In the Crossfire of History shines a light on women across the globe who are resisting the sociopolitical and economic injustices in their nation-states"--